PENGARUH PENGGUNAAN ABU SERABUT KELAPA (ASK) SEBAGAI BAHAN TAMBAH TERHADAP KUAT TEKAN BETON ALIR - Santoso Nugroho; Nurul Rochmah (LPPM Universitas Abdurrab, 2024)
Development in Indonesia continues to increase every year, this is due to the increasing population in this country. This construction requires important construction materials, such as concrete. Flowing concrete is a type of concrete that has a slump flow value of more than 19 cm, but still maintains the natural strength of the concrete according to ASTM C 1017 standards. Flowing concrete is usually used for placing thin sections or in areas of solid reinforcing steel to reduce handling costs, explained by (Dawood and Ramli 2010). To produce flowable concrete, it is necessary to use a superplasticizer so that the cement particles can be suspended evenly and separated into fine particles in the concrete mixture. Based on the research results, it shows that the addition of coconut fiber ash with percentages of 0%, 2.5%, 5%, 7.5% and 10% with superplasticizer of 1.5% of the cement weight to determine the compressive strength of the concrete. The coconut fiber ash test object used acts as an additive in the optimum concrete mixture. The sample used was a 15 x 30 cm cylinder for testing the compressive strength of coconut fiber ash at the age of 7 days, 14 days and 28 days. The test results showed that with the addition of coconut fiber ash, the compressive strength of the concrete experienced fluctuations up and down at mixed percentages of 2.5% and 5%, while at percentages of 7.5% and 10% it tended to decrease compared to normal concrete.